Community empowerment efforts in improving environmental health - Syaharuddin Syaharuddin; Glendy Ariando Salomon; Anggeraeni Anggeraeni (Edukasi Ilmiah Indonesia, 2024)
Community empowerment efforts are a crucial strategy in improving environmental health in the midst of global challenges such as pollution, climate change, and ecosystem damage. Methods such as education, training, active participation, and collaboration between related parties, communities can gain the knowledge, skills, and awareness needed to maintain a healthy environment. The results of these empowerment activities include increased community participation in environmental decision-making, behavior change towards sustainable practices, development of environmentally friendly communities, and broader collaboration in solving environmental problems. In conclusion, community empowerment efforts not only provide benefits in improving environmental health, but also strengthen community capacity in contributing to overall sustainable development. Synergy between various parties is the key to achieving significant and sustainable changes in maintaining environmental health for a sustainable future.